Contingent valuation of ecotourism in marine parks, Malaysia: implication for sustainable marine park revenue and ecotourism management - Yacob, Mohd Rusli; Radam, Alias; Awang, Khairil Wahidin; Shuib, Ahmad (IDOSI Publications, 2009)
The merging of environmental conservation and ecotourism development results in the establishment of marine parks. The environmental conservation approach recognize the right and influence of people in biological valuable areas, hence, more attention are given to human and biological preferences. The ecotourism development approach is linked with the environment to generate economic profitability in terms of ecotourism business activities. Information on visitor's willingness to pay provides useful guidelines sustaining on marine ecotourism resources. To determine willingness to pay (WTP) for conservation fees, contingent valuation surveys were interviewed to 215 visitors to Redang Island Marine Park, Malaysia, during April to July of 2007. The results of logit regression showed that the bid amount, respondent income level and local visitors were the most significant predictors of WTP. Results suggest that most visitors would be willing to pay conservation fee considerably higher than the current fee of RM5. The results indicate that visitors are willing to pay for conservation fee about RM7.8 and RM10.6 per visit for local and international visitors. The estimated present value of conservation benefits is estimated to be between RM4.25 mil to RM4.7 mil from the period of 1995 to 2005. Results of this study are very important in assists policy makers in management and operation for marine parks ecotourism especially on revenue mechanism.